Stator and rotor currents analysis of the inverted rotor induction motor - (:unkn) unknown (My University, 2009)
A new approach for the design and construction of inverted rotor induction motor is presented. In this paper we propose a novel approach for constructing special induction motor. Stator and rotor current characteristics of an inverted rotor induction motor have been investigated. This motor has mechanical revolving characteristics both rotor and stator. The induction machine could be described as a three input, three output object either stator or rotor side. It is possible to make measurement for definition of the stator rotor parameters on this type construction. The objective of this paper is to propose three different type operation classification and comparison of them. By comparing three different experimental operation values are carried out and shown clearly. Experimental data have been recorded by using Fluke 434 Harmonic Analyzer device.
Keywords: Blocked rotor test; Harmonic distortion; Inverted rotor induction motor; No-load test; Power quality; Rotating field; Rotor currents; Slip; Stator currents